Towards carbon neutrality & COP29 Baku / Azerbaijan - COP30 Belem / Brazil: Exploring the impacts of economic, environmental, social, and governance (ECON-ESG) factors on Climate Policy Uncertainty (CPU) for sustainable development - Cem Işık; Serdar Ongan; Jiale Yan; Hasibul Islam (Heliyon)
Climate policy is crucial in shaping global responses to environmental challenges and steering societies towards sustainable and resilient futures. Thus, in research study, we examine the impacts of Economic (ECONF), Environmental (ENVF), Social (SOCF), and Governance (GOVNF) factors, as well as the combined (ECON-ESG) factors, on Climate Policy Uncertainty (CPU) at the global level. The new ECON-ESG form of sustainability, defined in this study, refers to the holistic approach to sustainability by including economic factors (ECON) to traditional ESG factors. Empirical findings reveal that while environmental (E) and social (S) factors worsen the CPU, economic factors (ECON) improve it in the long run. Governance (G) factors have no impact on the CPU. While a 1 % increase in E and S increases the CPU by 22 % and 27 %, the same percentage increase in ECON decreases it by 40 %. These results clearly show that analyses conducted only through the conventional form of ESG may be insufficient and inaccurate in analyzing the effects on the CPU. Our study's result should not be considered limited to the CPU only, and it will be helpful to use this proposed form, ECON-ESG, as a more comprehensive sustainability concept in sustainability studies since it also incorporates economic factors. This approach will enable policymakers to look at climate policies through a holistic sustainability lens with ECON-ESG. These results show that policymakers should adopt a holistic sustainability approach that includes economic factors when shaping climate policies.